A Gravity Equation for Indonesian Cocoa High Value-Added Products to Selected Middle-East Countries - Perwira, Abi Revyansah (Jurnal Akuntansi, Manajemen dan Ekonomi, 2023)
Indonesia’s export products are still dominated by raw materials and semi-finished products from the mining and agriculture sectors. Indonesia needs to expand its high-value-added products. Through the Making Indonesia 4.0 program, Indonesia makes efforts to develop its food and beverages manufacturing industry sub-sector, especially processed cocoa products. The previous papers did not research the export of Indonesian high-value-added cocoa products individually and combined with other cocoa products due to some zero-trade observations. This paper attempts to analyze the export of Indonesian cocoa products with HS code 1806 to selected Middle-east countries by utilizing an augmented gravity equation from 2011 to 2020. The Middle-east countries are chosen because some of them have high GDPs and have a long good bilateral relationship with Indonesia. Since there are some zero-trade observations, this paper applies PPML method to solve the gravity equation. Based on the result, all independent variables positively influence the export products except the economic distance. The result also reveals that the export of Indonesian 1806 products has a potency to be expanded in the Middle-east markets since there is an indicator that the supply of high-value-added cocoa products still cannot meet the markets’ demand.